PKM Pemanfaatan Modul Berbantuan GeoGebra dalam Pembelajaran Aplikasi Integral SMA di Balikpapan - Suci Yuniarti; Tri Hariyati Nur Indah Sari; Husnul Khotimah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2019)
The community service activity is conducted in the form of a counseling about the use of GeoGebra-aided modul in integral application learning. This activity aims to add knowledge about the use of GeoGebra-aided modul in mathematics learning especially integral application learning to mathematics teachers. The implementation method consists of four stages namely preparation, action, evaluation and report. This one day activity were attended by 26 mathematics teachers from elementary school, junior and senior high school and vocational school in Balikpapan at the 7th Floor G Building of Balikpapan University. The presented material consists of the use of GeoGebra-aided modul in integral application topic namely area of plane regions and volume of solids of revolution. This community service activity run well and smoothly and in accordance with the planning. Based on the carried activities, it is expected for mathematics teachers to create learning modules that appropriate with their students’ conditions in the class and integrate various multimedia to support their mathematics learning process.